The relationship between knowledge of HIV/AIDS and sexual behaviour among care workers (HCWs) in General Hospital Ogoja - Onyedinachi, Okezie Enyinnaya (Stellenbosch : Stellenbosch University, 2011)
Thesis (MPhil)--Stellenbosch University, 2011.